2006
DOI: 10.1177/0363546505281240
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Ulnar Collateral Ligament Insufficiency of the Elbow in Female Athletes

Abstract: This study demonstrated excellent overall results in 16 and good results in 3 female patients after medial elbow repair or reconstruction. Women appear to be able to consistently return to a high level of function after repair or reconstruction for medial elbow instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 24 publications
(55 reference statements)
1
64
0
4
Order By: Relevance
“…Repair of the ligament, especially in the absence of secondary pathologic changes, should allow a more rapid return to sports than will the standard reconstruction. 4 In 1981, Norwood et al 20 reported on 4 male patients undergoing primary repair of the ulnar collateral ligament after acute disruption. All patients were able to return to previous activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repair of the ligament, especially in the absence of secondary pathologic changes, should allow a more rapid return to sports than will the standard reconstruction. 4 In 1981, Norwood et al 20 reported on 4 male patients undergoing primary repair of the ulnar collateral ligament after acute disruption. All patients were able to return to previous activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our return-to-sport percentage is similar to recent reports and supersedes some other studies on undergoing reconstruction (68%-81%). 4,5,8,14,23,25,27 Studies have suggested that previous surgery may have a detrimental effect on outcome. 8,27 This was not noted in our study, but only 3 of the patients had previous surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There were six complications, two of which required return to the operating room all occurring in athletes who were able to return to sport. A recent systematic review identified three clinical series with a total of 92 patients undergoing MUCL repair including this and older series and reported similar results [64,69,63,67].…”
Section: Discussionmentioning
confidence: 61%
“…30 Recent studies have reported 90% to 95% rates of return to sports. [32][33][34][35] UCL reconstruction has become the gold standard for surgical treatment for UCL insufficiency.…”
Section: Medial Distraction Injury: Uclmentioning
confidence: 99%